A Study on the Management of Buah Hati Bunda Day Care in Pekanbaru - Chairilsyah, Daviq (FKIP-Universitas Riau, 2019)
Early childhood education is a coaching effort to the children from birth to six years old by carrying out stimuli of education in order to help physical and spiritual growth and development and they also have readiness to enter further education. Day care is one of early childhood education services for children aged 0-6 years. This research was to find out how the description of Buah Hati Bunda Day Care management. In addition, the object of research was day care of Buah Hati Bunda by providing 8 indicators and 22 sub-indicators to fulfill the management. The quantitative descriptive method was used to find out the description of the day care management. Data collection techniques used are using observation sheets. Based on the data analysis obtained the percentage of8 indicators: 1) physical is 85% and it is categorized into excellent level,2) toys and equipment is 75.3% and it is categorized into good level, 3)tutor is 80% and it is categorized into excellent level, 4) daily activitiesare 100% and it is categorized into excellent level, 5) tutor qualifications are 37.5% and it is categorized into poor level, 6) adult interaction is75% and it is categorized into good level, 7) relationship with the parents is 100% and it is categorized into excellent level, 8) licensing andaccreditation is 100% and it is categorized into excellent level. From the data, it can be concluded that the management of Buah Hati Bunda Day Care is categorized into good level.